The Influence Of Promotion, Customer Experience And Word Of Mouth On Purchasing Decisions At Boss Café Bayangkara Medan - Muhammad Yusuf; Ari Prabowo (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The restaurant business in Indonesia has always been dominated by foreign market share. Without looking far, busy centers such as malls, for example, are currently filled with restaurants from western countries or China. Starting from fast food restaurants to restaurants that provide full course menus. The population continues to increase, meaning the level of human need for food also continues to increase. Especially in the restaurant sector, it is currently showing very good development and is a business prospect that is progressing rapidly and increasing. The aim of this research is to find out whether promotions partially have a significant effect on purchasing decisions at Boss Cafe Bhayangkara, as well as knowing the influence of Customer Experience on purchasing decisions, and knowing simultaneously on Word of Mouth and the existence of Promotions in Customer Experience, Word of Mouth which has an influence on purchasing decisions at Boss Café Bhayangkara. In this research method, it is quantitative. The population in this research is all Boss Café Bhayangkara customers. The sampling technique is based on criteria (considerations). The sample parameters are: All Boss Café Bhayangkara customers, all Boss Café Bhayangkara customers came back using the Zikmund formula to reduce the sample size, so the sample in this study was 96 people and rounded up to 100 people. The results obtained from this research show that: 1) Promotion, 2) Customer Experience, 3) Wort of Mouth, 4) Purchase decisions. Basically, it shows how far the influence of an independent variable individually is in explaining the dependent variable.